Kidney transplant from hepatitis C viremic donors into aviremic recipients and risk for post‐transplant BK and cytomegalovirus infection. Issue 4 (13th July 2022) - Daloul, Reem; Schnelle, Kendra; Von Stein, Lauren; Logan, April; Singh, Priyamvada; Yenebere, Priya; Pesavento, Todd; Washburn, Kenneth
Abstract: Background: kidney transplantation from Hepatitis C virus (HCV) viremic donors to uninfected recipients is associated with excellent short‐term outcomes. However, HCV viremia might be associated with an increased risk for post‐transplant viral complications. Methods: We designed a retrospective study of HCV‐negative kidney‐only transplant recipients between 2018 and 2020. Recipients were grouped into group 1; HCV‐negative donors, and group 2; HCV‐viremic donors. Patients were matched 1:1 using propensity score. The primary objectives were to compare the incidence of cytomegalovirus (CMV) viremia ≥ 200 ml/IU, and BK viremia ≥1000 copies/ml between the groups. Secondary outcomes included group comparison of CMV disease, BK viremia ≥10 000 copies/ml, and 1‐year patient and allograft survival. Results: The study included 634 patients in group 1, and 71 patients in group 2. Sixty‐five pairs of patients were matched. Incidence of CMV viremia (33.3% vs. 40.0%, p = .4675), and BK viremia (15.9% vs. 27.7%, p = .1353) did not differ significantly between groups in the matched cohort. Incidence of CMV disease (81.0% vs. 76.9%, p = 1.000), and BK viremia ≥10 000 copies/ml (9.5% vs. 16.9%, p = .2987) were comparable between groups. There was no difference in the 1‐year patient or allograft survival between groups. Conclusion: kidney transplant from HCV‐viremic donors is not associated with increased risk for BK or CMV viremia. Abstract :